2015
DOI: 10.1371/journal.pone.0138901
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ADL Disability in Older Persons, Physical Activities as a Protective Factor and the Need for Informal and Formal Care – Results from the SNAC-N Project

Abstract: BackgroundThe aim of the study was to examine 1) the incidence of disability in Activities of Daily Living (ADL), in persons 78 years and older 2) explore whether being physical active earlier is a significant predictor of being disability free at follow-up and 3) describe the amount of informal and formal care in relation to ADL-disability.MethodsData were used from a longitudinal community-based study in Nordanstig (SNAC-N), a part of the Swedish National Study on Aging and Care (SNAC). To study objectives 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
5
28
3
Order By: Relevance
“…Still, the magnitude is not very high and may be interpreted as a factor of good equality in Swedish nursing homes. Eighty‐five percent of residents in this representative sample of nursing homes in Sweden were dependent in some activity of daily living that is common in older ages, and these are figures found in other studies . Two‐thirds of residents were cognitively impaired which is in line with previous studies and common when dementia is present .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Still, the magnitude is not very high and may be interpreted as a factor of good equality in Swedish nursing homes. Eighty‐five percent of residents in this representative sample of nursing homes in Sweden were dependent in some activity of daily living that is common in older ages, and these are figures found in other studies . Two‐thirds of residents were cognitively impaired which is in line with previous studies and common when dementia is present .…”
Section: Discussionsupporting
confidence: 89%
“…Eighty-five percent of residents in this representative sample of nursing homes in Sweden were dependent in some activity of daily living that is common in older ages, and these are figures found in other studies. 22,41,42 Two-thirds of residents were cognitively impaired which is in line with previous studies and common when dementia is present. 4,9,[43][44][45][46] To our knowledge, there are only few previous studies that have analyzed resource use measured in hours per…”
Section: Discussionsupporting
confidence: 88%
“…2931 In cross-sectional and shorter-term follow-up studies, low physical activity is associated with lower fitness, more frailty, higher disability, and poor health. 3235 No long-term randomized trials have addressed whether changes in health behavior in middle age lead to late-life differences in physical activity. Also, observational follow-ups on this topic are rare, and we are not aware of other studies relating long-term leisure-time physical activity differences in younger adulthood to objectively measured physical activity/inactivity in later years.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, complications regarding the functional autonomy and the mental impairment tend to increase, this was observed by Sjörlund et al (39) , who studied the functional autonomy in older adults of both sexes, aged 78 years or older, with dementia, whom received care through non-formal activities, such as dancing. These authors found that the incidence rate to increased loss of functional autonomy was greater in women.…”
Section: Discussionmentioning
confidence: 89%